Pengaruh Inflasi, Suku Bunga, dan Nilai Tukar Rupiah Terhadap Harga Saham Perusahaan Sub Sektor Perbankan yang Terdaftar Di Bursa Efek Indonesia - Afrita Rahmayanti; Siti Ning Farida (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to examine the simultaneous and partial effect of Inflation, Interest Rate, and Rupiah Exchange Rate on stock prices of companies listed in the banking sub-sector on the Indonesia Stock Exchange. This type of research is quantitative research and uses secondary data. The total population is 20 banking sub-sector companies that use time-series data starting from January 2016 to October 2021 with the saturated sampling technique method. The analysis technique used is the multiple linear analysis techniques. Test the hypothesis with the F-test and T-test. The results of the simultaneous research (F-test) are known that inflation, interest rates, and the rupiah exchange rate have a significant effect on the stock prices of companies in the banking sub-sector. Partially (T-test) Inflation does not affect the stock prices of companies in the banking sub-sector. Interest rates have a significant negative effect on the stock prices of companies in the banking sub-sector. Meanwhile, the Rupiah Exchange Rate has a significant positive effect on the stock prices of companies in the banking sub-sector